(untitled) (Research, Society and Development, 2022)
The achievements of women have grown over time, however, it is a fact that society has always sought to maintain total female submission for many years, highlighting the activities carried out by men as the most important. Domestic violence against women is part of several discussions among social problems today, despite the fact that it has been going on for years in history. Violent deaths of women are a global phenomenon due to their fragility and vulnerability in relation to men. The Maria da Penha law enacted in 2006 came with the objective of curbing and preventing domestic violence against women. Based on this assumption, the present study aimed to characterize the phenomenon of domestic violence against women from to describe reasons that imprison women in a condition of submission to the aggressor. For that, a bibliographic and documentary research of quantitative and descriptive character was carried out through the use of data published in online newspapers of the aforementioned municipality. The results point out the aggressors as individuals under the effect of psychoactive substances such as drugs and alcohol, jealous, stressed and unhappy with the end of the relationship; the aggressions are summarized in physical and psychological, accompanied by sexual, patrimonial and moral violence. The reasons that keep women in a condition of submission to the aggressors are social factors such as unemployment, lack of financial means to support themselves and their children, fear, lack of family support, affective dependence and the hope that the partner will change their behavior.